2016
DOI: 10.9788/tp2016.4-13
|View full text |Cite
|
Sign up to set email alerts
|

Eventos de vida positivos e negativos em crianças

Abstract: ResumoPesquisas sobre bem-estar subjetivo e satisfação de vida em crianças também investigam o autorrelato de eventos de vida. Este estudo buscou investigar quais eventos de vida, positivos e negativos, são mais frequentes na vida das crianças, na sua percepção, e realizar comparações por sexo, por tipo de escola e por faixa etária. Duzentas crianças (5 a 12 anos) foram individualmente entrevistadas, e as falas transcritas foram analisadas mediante análise de conteúdo. Os eventos de vida positivos mais citados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…This self-assessment has been analyzed as a positive indicator of psychological adjustment in adolescent samples, associated with positive developmental outcomes. When examining the impact of different developmental contexts on subjective happiness, children reported that the most important areas were family climate, leisure time, friendship, school adjustment and receiving gifts [ 12 ]. Thus, more research is necessary about leisure as a key element for adolescent development [ 8 ], since leisure time may provide many pleasant experiences to enhance subjective happiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This self-assessment has been analyzed as a positive indicator of psychological adjustment in adolescent samples, associated with positive developmental outcomes. When examining the impact of different developmental contexts on subjective happiness, children reported that the most important areas were family climate, leisure time, friendship, school adjustment and receiving gifts [ 12 ]. Thus, more research is necessary about leisure as a key element for adolescent development [ 8 ], since leisure time may provide many pleasant experiences to enhance subjective happiness.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have concluded that spending many hours in front of a screen negatively influences children's physical and mental health [20][21][22]. Furthermore, although free time may constitute a source of personal satisfaction [12], time spent by adolescents in unstructured activities with friends without adult supervision is considered a risk factor for engaging in antisocial behavior [23]. Contrarily, some studies have underlined that warm affective bonds within the family and positive peer relationships are fundamental sources of perceived well-being [24,25].…”
Section: Introductionmentioning
confidence: 99%